Rhetoric of Justice Ruth Bader Ginsburg: Brief Comparison of the Language of the Advocate with the Language of the Justice - Peratis, Kathleen (Columbia Journal of Gender and Law, 2013)
I worked with and for Justice Ruth Bader Ginsburg in the 1970s at the ACLU. I have been in private practice since then, mostly practicing employment law. As I was considering what to speak to you about today, I decided to look back at the briefs that Justice Ginsburg wrote in the 1970s. And as I read them, it occurred to me that there’s a very interesting difference between the way she framed her arguments those thirty-five years ago, the language she used, the results she sought then as an advocate, and the way she does those things now as a judge.